Immediate loading of multiple splinted implants via complete digital workflow: A pilot clinical study with 1‐year follow‐up. (26th April 2019) - Jiang, Xi; Lin, Ye; Cui, Hong Y.; Di, Ping
Abstract: Background: Complete digital workflow attracts more attention in implant dentistry. Objectives: To explore the feasibility and short‐term clinical results of immediate loading of multiple implants with fixed temporary bridges (2‐4 teeth span) by complete digital workflow, and to evaluate the three‐dimensional (3D) deviation of digital impression comparing with traditional impression method. Material and Methods: A total of 31 partial edentulous patients (16 females and 15 males) were recruited in this study. Digital impressions were taken immediately after implant placement, and implant‐supported splinted temporary bridges were fabricated through a full digital approach (model free) and delivered within 24 hours. Final restorations were finished 4 months after surgery via traditional impression technique. Subjects were followed 1 year after treatment. 3D impression deviations were analyzed by comparing the digital and conventional impression methods. Time costs for the full digital approach were recorded. Implant survival rate, marginal bone levels were evaluated. Results: All the recruited subjects finished this study. Seventy‐four implants were surgically placed and immediately loaded with 34 temporary bridges fabricated through a full digital approach. Digital impression deviation compared with traditional impression method was 27.43 ± 13.47 μm. Time costs for chair side and laboratory were 32.55 ± 4.73 and 69.30 ± 10.87 minutes, respectively. Marginal bone alterations were −1.58 mm and −1.69 mm at the time of 4 and 12 months after surgery. The implants had a survival rate of 100% at the 1‐year follow‐up time. Conclusions: Immediate loading of multiple implants in partial edentulous (2‐4 teeth span) patients with full digital approach is clinically applicable. The 3D discrepancy between digital and traditional impression is within clinical acceptable range.